Evaluasi Tata Kelola Keamanan Informasi menggunakan COBIT 5 pada Domain APO13 dan DSS05 (Studi pada PT Gagas Energi Indonesia) - Yauma Dzikri Imany; Widhy Hayuhardhika Nugraha Putra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT Gagas Energi Indonesia is one company that applies Information Technology (IT) to support its business processes. IT management activities within PT Gagas Energi Indonesia are carried out under the HR & IT Department through the IT Work Unit. Utilization of IT requires a lot of data and information to support ongoing business processes. The amount of data and information with confidential properties stored in IT needs to be ensured that the data and information stored on the IT that is implemented has been properly secured to prevent threats to the system that harm the business. The quality of information security management needs to be measured to ensure that the information technology applied is truly safe. Measurement of information security is done by comparing the achievements that have been achieved by the company and the desired achievement of the company. The method used in this study is qualitative by using the COBIT 5 framework with a focus on the APO13 process (Managing Security) and DSS05 (Managing Security Services). Data collection is done by observing and using assessment sheet instruments and interviews. Based on the results of the study, the two processes have reached level 2 (Managed Process), while the level of achievement desired by the company is at level 3 (Estabilished Process). So that there is a gap (gap level) of 1 level in each process. Next will be given a number of recommendations based on the findings of the study by considering existing gaps.